How is presupposition accommodation constrained, again? - Benbaji-Elhadad, Ido; Doron, Omri (Proceedings of the Amsterdam Colloquium, 2024)
According to the satisfaction view, presuppositions are conditions on the discourse context which must be satisfied for the utterances carrying them to be felicitous. These conditions can either hold in the context prior to the utterance of a presuppositional sentence, or they may be added to the context post-hoc, via a process known as presupposition accommodation, after a presuppositional utterance has been introduced. Since Lewis (1979), it is known that controversial or surprising information resists accommodation. However, this apparent constraint does not seem to follow from the theory of discourse underpinning the satisfaction view. Building on a proposal by Doron and Wehbe (2022), we argue that the facts can be derived within that theory without stipulating any primitive constraints on accommodation, once we take into account independent considerations regarding the structure of discourse.